Evaluating a Modified Use of the Kaiser Permanente Early-onset Sepsis Risk Calculator to Reduce Antibiotic Exposure: a Retrospective Study - Ahmed Mustafa; Mohammed Yasir Alhindi; Faisal Ghazi Almalki; Saif Al Saif; Abdulaziz Almalahi; Mawaddah Hesham Alsaegh; Mansour Abdullah AlQurashi (BMJ Publishing Group, 2024)
Background Early-onset neonatal sepsis (EONS) remains an important disease entity due to very serious adverse outcomes if left untreated. Lack of diagnostic tools in identifying healthy from diseased neonates, and clinicians' fear of the missing positive-culture sepsis babies, or babies with clinical sepsis have led to overtreating and unnecessary antibiotic exposure. Kaiser Permanente EONS risk calculator is an internally validated tool that can predict EONS. This sepsis risk calculator (SRC) classifies neonates into three subgroups: (1) ill-appearing, (2) equivocal and (3) well-appearing. We propose a modification to this tool that aims to use it solely for well-appearing babies. This modification represents a more conservative approach to decrease antibiotic exposure and offers an alternative for those hesitant to fully implement this tool.Methods This is a dual-centre retrospective study where data were extracted from the electronic medical records. Our primary outcome was to validate the modified use of the SRC with a two-by-two table. Specificity, negative predictive value and expected antibiotic reduction were used to evaluate the tool's feasibility.Result Among 770 babies suspected of EONS, the feasibility of the modified use was tested. The expected antibiotic exposure reduction rate on the modification was 40.4% overall. The proposed modification resulted in a specificity and negative predictive value of 99.28% (95% CI: 97.92% to 99.85%) and 99.5% (95% CI: 99% to 99.8%), respectively.Conclusion The modified use of the sepsis risk calculator has shown that it can safely reduce antibiotic exposure in well-appearing babies. The modified use is used as a 'rule out' test that can identify very low risk of EONS babies, and safely minimise antibiotic exposure. Further prospective studies are needed to examine the efficacy of this use, and quality improvement projects are required to evaluate its applicability in different clinical settings.